THE MONITORING OF SOILS ON THE LAND AREAS AS INFORMATION SUPPORT FOR THE REGISTER OF SOIL RESOURCES AT THE LOCAL LEVEL - D. V. Belobrova; D. A. Shapovalov (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
The results of large-scale (1 : 5000) soil mapping of allotments (garden non-commercial partnerships) located on the territory of Meshchera lowland of Noginsk district of Moscow region are considered. The investigations showed that the initial soils located on the territory of the allotments have suffered the significant transformation since the allotments were created. Predominantly soddy podzolic soils with the different degree of surface or ground gleization, and also boggy soils were transformed into the agro-soddy podzolic soils and agrozems. The most significant changes occurred within soils in areas of intensive development where the implementation of organo-mineral fertilizers, green manures, formed agrogenic (hummock) micro-topography, manmade microstructure of the soil cover. Compared to the natural soil profile, they are characterized by a neutral pH, high and medium content of mobile phosphorus, poor in exchange potassium. Soils with the medium humus content (3–5% humus) prevail in this area. We separated clusters characterized by the agro-chemical and morphological properties of soils reflecting the classification at the level of subtype. The revealed changes reflect the growth of productivity and quality of the allotment soils and determine the expediency of soil parameters consideration in the basic documents providing the register of soil resources at the local level.